Design of Access Control and Positioning System based on Beacon - Kwak, Eun-Shin; Kim, Eon-Gon (International Journal of Engineering and Technology, 2018)
Background/Objectives: Smart devices combine GPS (Global Positioning System) and Wi-Fi signals to precisely identify the user's location outdoors. Also, it is possible to provide a navigation function for displaying on a service such as a map by using this technology. However, it is impossible to precisely locate the user because service provision for indoor location confirmation is difficult to receive GPS. Therefore, it is necessary to study and design the system more accurately by applying various technologies.Methods/Statistical analysis: Many infrastructure technologies are being researched and utilized to improve indoor location and accuracy. Typical existing services include Wireless Local Area Network, Bluetooth, Ultra-wide Band, Ultrasonic sound, and Beacon. Based on these technologies, users are located inside the building and provided services based on their location. However, it is pointed out that a precise positional measurement is not performed, an error rate is large, and an error occurs in the result due to the influence of the surrounding environment. Therefore, in this paper, we design a system for indoor location and access control by applying low power Bluetooth based beacon. Beacon is used in the proposed system design because it has less battery consumption of smartphone than the existing Bluetooth version.Findings: In this paper, we have carried out a study to improve the accuracy and reliability of the indoor positioning system service which is rapidly activated. To do this, we designed a system for locating users in indoor space using low power Bluetooth based beacon and heterogeneous sensor. Also, we propose a security policy that can efficiently control access to facilities based on indoor location. As a result, Beacon, ultrasonic sensors, Wi-Fi, and motion sensors were designed as integrated modules, and access control was performed by locating the users in each zone. In addition, a system design methodology for user access control, behavior restriction, and user behavior pattern analysis is proposed by combining user room location information and security policy.Improvements/Applications: Finally, we designed a protocol and software for communication between beacon and mobile, and implemented a smooth communication module. In addition, we conducted a study on indoor location using Beacon for precise location. To do this, hybrid positioning algorithms using Beacon and various devices (ultrasonic sensor, Wi-Fi, motion sensor) were studied. And, the algorithm was designed for the situation - based indoor location positioning technology using heterogeneous or various sensors. Based on the results of the study, we propose a system policy that improves the accuracy of indoor location and enhances the security of access control.Â Â